Non-Driving Related Activities Inside an Automated Vehicle Among Malaysia Passengers - Mohammad Izhar Sulaiman; Nidzamuddin Md Yusof; Juffrizal Karjanto; Muhammad Zahir Hassan; Syabillah Sulaiman; Zulhaidi Mohd Jawi; Khairil Anwar Abu Kassim (Universitas Muhammadiyah Magelang, 2023)
The advancement of automotive technology has led to the development of automated vehicles. The trend of passengers performing non-driving-related activities during travel was expected to continue in the future of automated vehicles. It is essential to discover the type of activities that the users prefer to improve the interior design of an automated vehicle. Past studies show that every country has different preferred non-driving related activities. The main objective of this study is to collect data on preferred non-driving related activities, specifically by Malaysians, using online questionnaires. 293 respondents answered the questionnaires in six (6) months. As a result, the top three (3) non-driving related activities in Malaysia are listening to music, calling or texting, and interacting with others. In addition, the most preferred seating position as a passenger, the most suitable travel duration to perform non-driving related activities uninterrupted, and the preferred seating configuration of the automated vehicle were also discovered. The outcome of this study will add knowledge for designing better future automated vehicles suitable for Malaysian users.